Relationship between the level of knowledge with the degree of compliance with standard precautions biosafety staff nursing services for Neurology and Neurosurgery, National Neuroscience Institute. - Quispe Masías, Felicitas (2019)
Objective: To determine the relationship between the level of knowledge and degree of compliance with standardprecautions biosafety staff nursing services for Neurology and Neurosurgery, National Neuroscience Institute,October 2011 to March 2012. Material and Methods: The study was quantitative, correlational and crosssectional. The sample was composed of 51 nursing technicians of the National Institute of Neurological Sciences,selected by non-probability sampling, for convenience. The information was generated through a questionnaireand an observation guide elavorados by the authors. Both instruments were subjected to the judgment of expertsand the reliability test under Kudder Richardson coefficient ( 0.77). Results: The results show that 64.7% ofnursing technicians have an average level of knowledge standard biosafety precautions, 23.5% have a low leveland only 12% a high level. Regarding the level of compliance with standard precautions biosecurity, which is43.1% a medium level, 35.2% have a high level and 21.5% low. Conclusions: According to the nonparametricPearson correlation was found between the two variables (0.068 ) being significant ( p> 0.05 ).